A identificação dos educandos com notáveis desempenhos na educação básica sob a perspectiva de trabalho do Núcleo de Atividades de Altas Habilidades/Superdotação de Goiás - Silva, Ariovaldo Simões (2020)
Currently, a significant number of students with remarkable performances are invisible in the classrooms of the basic education. Whether due to lack of knowledge on the part of teachers, the characteristics that these students have or even, because they are disowned the school environment given the erroneous idea that they have great potential, they are devoid of special educational needs. The fact is that, because they are not properly recognized for their extraordinary performance in the teaching and learning process, they are devoid of opportunities that enable the enrichment of their skills and talents in the area of knowledge of interest. The present research had the general objective to then contribute to the process of identifying students with characteristics of High Skills / Giftedness based on the continuing education of teachers of the course “Fundamentals in High Skills / Giftedness” offered by the Nucleus of High Skills Activities / Giftedness of Goiás (NAAH/S). Its approach was qualitative, in the form of a case study based on a group of teachers and other education professionals enrolled and attending the course in question. Participant observation was chosen as the main methodological procedure and the work carried out in three stages: (1st) survey of legal documents, books, articles , theses and dissertations that support the theme for the construction of the structural basis of the research; (2nd) conducting field research; (3rd) creation of the educational product, a Blog with texts to support the teacher which helps him to identify himself more clearly and securely in education with high skills / giftedness, and also a form to indicate this type of education for NAAH/S-GO which will subsequently constitute a database. To carry out this investigation, was elected as a theoretical framework Joseph Renzulli and authors whose researches contributed to the universe of High Skills / Giftedness. The results showed that most of the educators participating in the course do not understand about the process of identifying students with characteristics of High Skills / Giftedness due to lack of information and training on the subject. However, the continuing education course made it possible to raise the awareness of these teachers and other education professionals, to carry out this identification. Therefore, we consider that understanding about High Skills / Giftedness in its various nuances, based on continuing education, is the first step to identify students who present characteristics of giftedness and, from then on, contribute to who receive enriching opportunities. with a view to developing its potential.